Historical Analysis: Contemporary Image and Representation of Sultan Muhammad Bin Tughlaq Among Ziauddin Barani’s Texts - Wafiullah Aminzai; Dadman, Enayatullah (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the most important domain in human knowledge is Historiography which donate a lot theory in the field, the two most well-known schools are the Persian and Arab historiographies. The Arab historiography is the first. From the time when Islam was established in India at the beginning of the 13th century until the great Mughal Empire fell, two significant contributions to the development of Persian history in India during the Sultanate Period, notably during the authority of the Tughluq dynasty, are the